Mucin-1 expression in endometrial tissue of Macaca nemestrina during mid-luteal phase after controlled-ovarian hyperstimulation - Nurhuda Sahar; Ponco Birowo; Kusmardi Kusmardi; Diyah Kristianty; Karina Rahmaningrum; Adriana Viola Miranda; Afif Rasyad; Vivitri Prasasty (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sahar N, Birowo P, Kusmardi, Kristianty D, Rahmaningrum K, Miranda AV, Rasyad A, Prasasty VD. 2021. Mucin-1 expression in endometrial tissue of Macaca nemestrina during mid-luteal phase after controlled-ovarian hyperstimulation. Biodiversitas 22: 1927-1933. Endometrial receptivity is one of the factors for successful implantation in pregnancy. Controlled ovarian hyperstimulation (COH) is a required step of in vitro fertilization (IVF), one of the standard procedures to overcome infertility. Exogenous gonadotropin hormones from COH provoke the secretion of estrogen and progesterone from the ovaries in higher amounts. The supraphysiological environment could impact the endometrial receptivity of the implantation process. Mucin-1 (MUC1) can be used as a marker to indicate alterations in the endometrial tissue. Therefore, this study aimed to investigate the alteration of mucin-1 expression in endometrial tissue of Macaca nemestrina after COH protocol. This study used endometrium tissue of M. nemestrina embedded with paraffin as tissue blocks. The subjects were 15 female macaques in reproductive age (8-10 years old) with a history of producing offspring. These macaques were classified into four groups based on the COH protocols, which consist of administering gonadotropin-releasing hormone (GnRH) agonist and recombinant FSH (r-FSH) with dosages of 30 IU, 50 IU, 70 IU (intervention groups), and no r-FSH (control group). The stimulations were administered for 14 days during the mid-luteal phase. Moreover, tissue staining was done by using immunohistochemistry. Mucin-1 expression was analyzed manually for glandular and luminal compartments and automatically for the stromal compartment by Red Green Blue (RGB) measure plugin as a color image from ImageJ software. The expression of mucin-1 was counted semi-quantitatively as H-score. Mucin-1 expression differences in endometrial tissue were assessed by one-way ANOVA with a significant difference found in the glandular part and insignificant results found in luminal and stromal parts. Pearson correlation test was also performed to determine the relationship of steroidal hormones and mucin-1 expression in glandular and luminal compartments. Both correlations were statistically insignificant. However, a positive correlation was found with the glandular compartment and a negative correlation with luminal compartment. As the subject species, M. nemestrina is limited for research utilization in our country, small number of subjects becomes a limitation of this study. Further studies need to be conducted to deepen the understanding of the regulation of mucin-1 expression, particularly by the altered concentrations of steroidal hormones as a consequence of COH.